c-Met affects gemcitabine resistance during carcinogenesis in a mouse model of pancreatic cancer - Noguchi, Kozo (Oncol Lett, 2018)
Pancreatic adenocarcinoma is thought to develop from histologically identifiable intraductal lesions known as pancreatic intraepithelial neoplasias (PanINs), which exhibit similar morphological and genetic features to pancreatic ductal adenocarcinoma (PDAC). Therefore, a better understanding of the biological features underlying the progression of PanIN is essential to development more effective therapeutic interventions for PDAC. In recent years, numerous studies have reported that MET proto-oncogene receptor tyrosine kinase (c-MET) is a potential marker of pancreatic cancer stem cells (CSCs). CSCs have been revealed to initiate and propagate tumors in vitro and in vivo, and are associated with a chemoresistant phenotype. However, in vivo models using a xenograft approach are limited. In the present study, the morphological phenotype, molecular alteration and biological behavior of neoplasia in Pdx-1Cre/+, KrasLSL-G12D/+ and Metflox/flox and wild-type mice was analyzed. The results demonstrated that while oncogenic KrasLSL-G12D/+ increased PanIN initiation and significantly decreased survival rate compared with wild-type mice, no additive effect of c-Met receptor signaling on PanIN progression or prognosis was observed. Following gemcitabine administration, c-Met inhibition in Kras LSL-G12D/+ mice significantly decreased the total surface area of PanIN lesions and the number of anti-proliferation marker protein Ki-67 positive cells occupying PanIN lesions compared with Met+/+ mice. In conclusion, complete inhibition of the c-Met signaling pathway with chemotherapy may be useful for the treatment of pancreatic cancer.